PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA SMKN 1 PANGGUL KABUPATEN TRENGGALEK (Manajemen & Bisnis Jurnal, 2023)
This study aims to describe and analyze 1) the influence of leadership and work motivation on employee job satisfaction; 2) the influence of leadership and work motivation on employee performance; 3) the effect of job satisfaction on employee performance, and 4) the influence of leadership and work motivation on employee performance with job satisfaction as an intervening variable at SMKN 1 Panggul Trenggalek district. The research conducted at SMKN 1 Panggul Trenggalek district used a quantitative approach which collected data using a questionnaire with a total population and sample of 50 respondents. The data analysis technique used is path analysis, namely by knowing the direct and indirect effects of the independent variables on the dependent variable. Based on this, can it can be concluded that 1) leadership and work motivation have a significant influence on employee job satisfaction; 2) Leadership and Work Motivation have a significant influence on employee performance; 3) Job satisfaction directly has a significant effect on employee performance and 4) Leadership and work motivation directly and indirectly have a significant effect on employee performance with job satisfaction as an intervening variable at SMKN 1 Panggul Trenggalek district.